Resilience, ambiguous governance, and the Ukrainian refugee crisis: Perspectives from NGO leaders in the Czech Republic - Tara Kolar Bryan; Monica Lea; Vladimír Hyánek (Central European Economic Journal (CEEJ), 2023)
The Russian invasion of Ukraine in late February of 2022 caused a humanitarian refugee crisis on a scale unseen since World War II. The scale and speed at which refugees surged into other European countries required significant resources to respond to this influx. This study explores the perspectives of those working in NGOs about the resilience of their organisations in responding to the Ukrainian refugee crisis in the Czech Republic. Drawing on interview data collected at the beginning of the refugee response in the Czech Republic between February and June of 2022, our findings suggest that NGOs face capacity and governance challenges, and these system-level barriers inhibit NGO resilience and their ability to respond effectively to the Ukrainian refugee crisis in the long term. These lasting effects influence NGO resilience in the face of the unprecedented Ukrainian crisis. Despite these barriers, NGOs acted with flexibility and agility in delivering humanitarian assistance to Ukrainian refugees in the first few months of the crisis. The findings from this study indicate NGOs engage in organisational resilience strategies within a policy and governance system that lacks the adaptability and coordination needed to be resilient.
Keywords: H12; Z18; 330; NGOs; resilience; capacity; migration; Ukraine